(untitled) (Research, Society and Development, 2020)
The various types of cancer have been the second largest cause of mortality in most countries, and the use of tumor markers for cancer diagnosis is a relevant issue for the health area. This study aims to demonstrate the importance of laboratory tests that use non-invasive methods and that can identify alterations in several organs of the human body, thus being able to analyze data related to tests used that help in the diagnosis of cancer, with simple exams and with the cost of some exams relatively cheaper than images, thus being able to be performed by people of several social classes. and has as expected to instruct and raise awareness about the importance of the present study. A bibliographic study using as keywords "tumor markers" and biochemical exams" and using data from SCIELO (Scientific Electronic Library Online), articles published from 2001 to 2019, with the purpose of acquiring and instructing knowledge on the subject. The use of tumor markers.